Capability in Utilizing Social Media as a Promotion Strategy for Increasing the UMKM Economy - Luky Destianah (CIC Lembaga Riset dan Konsultan Sosial, 2021)
The business world in Indonesian is now expanding, including UMKM. A lot of MSMEs in Indonesian today can be used to support the country’s economy. Especially is it supported by the growing information technology. They include social media such as facebook, whatsapp, instagram, and the like, which can be used as promotional media for businesses. The fact is that micro business leaders lack the optimum understanding and optimally utilizing technology, which suggests that they lack the ability to read the business opportunities. If they can harness the technology optimally then surely the profit they get is absolute. Furthermore, people are more likely to know their business because of the unlimited social media reach, making it easier to be known to the public. From the data I’ve obtained, micro businesses are underulitizing the sophistication of current technology, especially for those who are old and have little knowledge. Then, the majority of women in business can not give much attention to their business because their something higher priority, such as family. As we know it is only natural for a women to take care of the household so that there is a gap between the male and the female. It is these gaps that prevent the use of information technology in the economic growth of MSMEs.